Temperature increase significantly enhances nociceptive responses of C-fibers to ATP, high K+, and acidic pH in mice - Tkachenko, Yurii; Khmyz, Volodymyr; Isaev, Dmytro; Maximyuk, Oleksandr; Krishtal, Oleg (Frontiers in Cellular Neuroscience, 2023)
It is well established that temperature affects the functioning of almost all biomolecules and, consequently, all cellular functions. Here, we show how temperature variations within a physiological range affect primary afferents' spontaneous activity in response to chemical nociceptive stimulation. An ex vivo mouse hind limb skin-saphenous nerve preparation was used to study the temperature dependence of single C-MH fibers’ spontaneous activity. Nociceptive fibers showed a basal spike frequency of 0.097 ± 0.013 Hz in control conditions (30 °C). Non-surprisingly, this activity decreased at 20 ºC and increased at 40 ºC, showing moderate temperature dependence with Q10 ~ 2.01. The fibers’ conduction velocity was also temperature-dependent, with an apparent Q10 of 1.38. Both Q10 for spike frequency and conduction velocity were found to be in good correspondence with an apparent Q10 for ion channels gating. Then we examined the temperature dependence of nociceptor responses to high K+, ATP, and H+. Receptive fields of nociceptors were superfused with solutions containing 10.8 mM K+, 200 µM ATP, and H+ (pH 6.7) at three different temperatures: 20, 30, and 40 ºC. We found that at 30 °C and 20 °C, all the examined fibers were sensitive to K+, but not to ATP or H+. At 20 °C, only 53% of fibers were responsible for ATP; increasing the temperature to 40°C resulted in 100% of sensitive fibers. Moreover, at 20°C, all observed fibers were silent to pH, but at 40°C, this number was gradually increased to 87.9%. We have found that the temperature increase from 20°C to 30°C significantly facilitated responses to ATP (Q10 ~ 3.11) and H+ (Q10 ~ 3.25), leaving high K+ virtually untouched (Q10 ~ 1.88 vs. 2.01 in control conditions). These data suggest a possible role of P2X receptors in coding the intensity of non-noxious thermal stimuli.